Jane Austen’s Persuasion and Romantic: A Literary Study - lateef Alnajm, Alaa; Majeed Alkhafaji, Weam (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates the relationship between the novel Persuasion, written by Jane Austen, and Romanticism. However, it increasingly studies how Austin writes her texts in a Romantic way by using unique narrative techniques to explore her ideas for the reader. It may very well be stated that the social structure of British society in the nineteenth century is comprehensively dissected and condemned at certain focuses by Jane Austen in her final finished novel, Persuasion. Fundamentally, it is accomplished through the focal idea about which the primary story plot advances. Meanwhile, the novel gives testimony regarding the change that the social structure of the general public goes through revolving around the adjustment in high society as a conclusion of the Industrial Revolution. The peruser is given two distinct choices of privilege: the aristocrats and the individuals from the Navy. The comparison between these two gatherings is explained via their varying virtues and relations of family members all through the novel.